Respostas
a) x² - 5x + 6 = 0
Δ = b² - 4.a.c
Δ = -5² - 4 . 1 . 6
Δ = 25 - 4. 1 . 6
Δ = 1
Há 2 raízes reais.
x = (-b +- √Δ)/2a
x' = (--5 + √1)/2.1
x'' = (--5 - √1)/2.1
x' = 6 / 2
x'' = 4 / 2
x' = 3
x'' = 2
b) x² - 8x + 12 = 0
Δ = b² - 4.a.c
Δ = -8² - 4 . 1 . 12
Δ = 64 - 4. 1 . 12
Δ = 16
Há 2 raízes reais.
x = (-b +- √Δ)/2a
x' = (--8 + √16)/2.1
x'' = (--8 - √16)/2.1
x' = 12 / 2
x'' = 4 / 2
x' = 6
x'' = 2
c) x² + 2x - 8 = 0
Δ = b² - 4.a.c
Δ = 2² - 4 . 1 . -8
Δ = 4 - 4. 1 . -8
Δ = 36
Há 2 raízes reais.
x = (-b +- √Δ)/2a
x' = (-2 + √36)/2.1
x'' = (-2 - √36)/2.1
x' = 4 / 2
x'' = -8 / 2
x' = 2
x'' = -4
d) x² - 5x + 8 = 0
Δ = b² - 4.a.c
Δ = -5² - 4 . 1 . 8
Δ = 25 - 4. 1 . 8
Δ = -7
Não há raízes reais.
e) 2x² - 8x + 8 = 0
Δ = b² - 4.a.c
Δ = -8² - 4 . 2 . 8
Δ = 64 - 4. 2 . 8
Δ = 0
Há 1 raiz real.
Neste caso, x' = x'':
x = (-b +- √Δ)/2a
x' = (--8 + √0)/2.2
x'' = (--8 - √0)/2.2
x' = 8 / 4
x'' = 8 / 4
x' = 2
x'' = 2
f) x² - 4x - 5 = 0
Δ = b² - 4.a.c
Δ = -4² - 4 . 1 . -5
Δ = 16 - 4. 1 . -5
Δ = 36
Há 2 raízes reais.
x = (-b +- √Δ)/2a
x' = (--4 + √36)/2.1
x'' = (--4 - √36)/2.1
x' = 10 / 2
x'' = -2 / 2
x' = 5
x'' = -1
g) -x² + x + 12 = 0
Δ = b² - 4.a.c
Δ = 1² - 4 . -1 . 12
Δ = 1 - 4. -1 . 12
Δ = 49
Há 2 raízes reais.
x = (-b +- √Δ)/2a
x' = (-1 + √49)/2.-1
x'' = (-1 - √49)/2.-1
x' = 6 / -2
x'' = -8 / -2
x' = -3
x'' = 4